2014
DOI: 10.3390/polym6082146
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide 11/Poly(vinylidene fluoride)/Vinyl Acetate-Maleic Anhydride Copolymer as Novel Blends Flexible Materials for Capacitors

Abstract: Abstract:A novel all-polymeric blend with high dielectric constant (K) has been developed by blending polyvinylidene fluoride (PVDF) and polyamide (PA11) via co-melt-pressing technology with a compatilizer vinyl acetate-maleic anhydride (VA-MA) copolymer. Adding a copolymer of vinyl acetate and maleic anhydride decreased the dielectric loss (tan δ ≈ 0.057) and increased the dielectric constant (K blend = 15). The blends show high dielectric constants, which give better frequency stability, and excellent mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…It can be seen from the figure that ε became greater with the increasing addition of PVDF, which can be explained by the influence of high dielectric properties of PVDF. There is an exception in PP/PVDF (60/40), due to the poorest interactions between two polymers according to our previous study [8][9][10]. A PVDF molecule contains two fluorine groups (-F) which show an intense polarity and have an orientation under the effect of external electric field, and the relaxation of the fluorine groups happens during the electric cycle.…”
Section: Dielectric Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…It can be seen from the figure that ε became greater with the increasing addition of PVDF, which can be explained by the influence of high dielectric properties of PVDF. There is an exception in PP/PVDF (60/40), due to the poorest interactions between two polymers according to our previous study [8][9][10]. A PVDF molecule contains two fluorine groups (-F) which show an intense polarity and have an orientation under the effect of external electric field, and the relaxation of the fluorine groups happens during the electric cycle.…”
Section: Dielectric Propertiesmentioning
confidence: 96%
“…Meanwhile, the application prospects of polymer blends is extensive, and they can typically be adopted by the modern electronic industry [6,7]. In our previous study, polyamide (PA) 11/PVDF and PA66/PVDF blends were reported as novel blends for capacitors [8][9][10]. Polyvinylidene fluoride (PVDF) is known as the polymer with the best dielectric properties, and has stable chemical and mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These PZT/PVDF composites could be widely applied in microelectronics devices fields. However, due to the lack of mechanical resistance and no flexibility, the combination of PZT particles with PVDF in micro scale is very difficult [11][12][13]. One of the most important key points of PZT/PVDF hybrid composites is to improve the interface of PZT in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the lack of mechanical resistance and no flexibility, the combination of PZT particles with PVDF in micro scale is very difficult. [11][12][13] One of the most important key points of PZT/PVDF hybrid composites is to improve the interface of PZT in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%